Formative assessment practices for pre-service teacher practicum feedback emerging research and opportunities - Richardson, Tony 1958-; Dann, Beverley; Dann, Christopher; O'Neill, Shirley (Advances in higher education and professional development (AHEPD) book series, 2018)
"This book explores the best ways of creating a sound training environment based on continuous feedback. It proposes new instruments for formative professional interactions. They focus on student teachers. It is grounded on sharing constructive feedback, and how this sense of non-judgmental feedback creates effective communities of reflective practice"--